Physical activity and breast cancer survivors: Importance of adherence, motivational interviewing and psychological health. (October 2018) - Pudkasam, Supa; Polman, Remco; Pitcher, Meron; Fisher, Melanie; Chinlumprasert, Nanthaphan; Stojanovska, Lily; Apostolopoulos, Vasso
Highlights: Adherence to exercise is important to improve cancer outcomes such as quality of life and depression. Programs promoting behavioral changes seem to be more effective ifbased on a theoretical framework. The theory of planned behavior and social cognitive theory, can be used to guide physical activity interventions. The self-determination theory and the transtheoretical models can be used to guide physical activity interventions. Motivational interviewing aids in physical activity behaviors. Abstract: Behavioral change theories have been used to support interventions that increase both motivation for and adherence to physical activity programs for breast cancer survivors. Most of the programs can improve psychological health-related quality of life. Depressive and anxious symptoms seem to be associated with some stressors, such as the perception of breast cancer, prognosis, long-term treatment-related side-effects and fear of cancer recurrence. Beyond physical fitness, several physical activity programs for breast cancer survivors have been reported to improve psychosocial wellness and life satisfaction. However, many physical activity programs have failed to motivate breast cancer survivors due to barriers such as general health issues and lack of time. More specifically, women may have little confidence in the benefits of physical activity and breast cancer outcomes. Therefore, engaging breast cancer survivors in physical activity is challenging for health care professionals. Herein, we identify cancer-related mental distress, coping style and behavioral theories applied to physical activity programs in breast cancer survivors. More specifically, we discuss the effectiveness and limitations of 3 psychological theories and 2 concepts related to behavioral change, including the theory of planned behavior, social cognitive theory, self-determination theory, transtheoretical model and motivational interviewing for physical activity adherence in breast cancer survivors.